Industrial and organizational psychology research and practice - Spector, Paul E. (John Wiley & Sons, Inc., 2021)
"Industrial/organizational or I-O psychology is an exciting field that has been enjoying continual growth in North America and throughout the industrialized world during its almost 100-year history. In 2019 U.S. News and World Report listed I-O Psychology as the second best science career. What began as a tiny subspecialty of psychology, known only to a few practitioners, human resources professionals, and professors, has grown to be one of the major specialties in psychology worldwide. This attention is due to two factors. First, I-O is concerned with the workplace, so its findings and principles are relevant to everyone who holds a job. Second, I-O has developed proven methods that organizations fi nd of value. I-O psychologists are often called on to help organizations develop a more efficient and healthier workforce. The field of I-O psychology has a dual nature. First, it is the science of people at work. This aspect ties it to other areas of psychology, such as cognitive and social psychology. Second, I-O psychology is the application of psychological principles of organizational and work settings. There is no other area of psychology in which a closer correspondence between application and science exists, making I-O a good example of how society can benefit from the study of psychology. The field of I-O is a large and diverse one. Many topics are covered, ranging from methods of hiring employees to theories of how organizations work. It is concerned with helping organizations get the most from their employees or human resources, as well as helping organizations take care of employee health, safety, and well-being. For this reason, a single text can provide only an overview of the major findings and methods that I-O psychologists use. The goal of this book is to provide such an overview, as well as a comprehensive understanding of the field. Each of the major areas that comprise I-O psychology is covered. Part 1 of this book provides an overview of the I-O field. Chapter 1 covers the nature of the field and its history. I-O psychology is discussed as both a practice and a science. The chapter describes what a career in I-O psychology involves and what it takes to become an I-O psychologist. Chapter 2 is an overview of the basic principles of I-O research methods. The remainder of the book is divided into four parts. Part 2 focuses on assessment. Chapter 3 discusses the assessment of jobs-called job analysis; Chapter 4 focuses on the assessment of employee job performance, and Chapter 5 explores the way in which employee characteristics are measured. Part 3 contains two chapters. Chapter 6 deals with the methods that organizations use to hire new employees. Chapter 7 follows those new employees, as well as experienced ones, through their training programs. The four chapters in Part 4 discuss the relationship between the individual and the organization. Chapter 8 covers theories of motivation. Chapter 9 focuses on how people feel about their jobs-their attitudes about the job and the emotions they experience at work. The topic of Chapter 10 is productive and counterproductive work behavior. Chapter 11 deals with occupational health psychology, a rapidly emerging field that is concerned with worker health, safety, and well-being. The final part of the book, Part 5, is concerned with the social context of work. Chapter 12 explores small work groups and work teams and their effect on the individual. Chapter 13 discusses leadership and supervision in the workplace. Chapter 14, the last chapter, takes an organization perspective. It covers organizational climate and culture, organizational development, and organizational theory."--Provided by publisher.